2009
DOI: 10.1007/s12257-008-0268-0
|View full text |Cite
|
Sign up to set email alerts
|

A new formulated stable papin-pectin aerosol spray for skin wound healing

Abstract: ^Äëíê~Åí= A new spray-on topical wound debrider composition consisting of 0.1% w/v papain immobilized in 6% w/v pectin gel was formulated for skin wound healing. The stability of the enzyme activity of this new formulated spray was compared with the 0.1% w/v papain in water solution at the refrigerated temperature of 4 and 75°C. Two aerosol propellants, air and nitrogen, were evaluated for their efficacy. The new formulated spray was then evaluated for its thermal stability under air and N 2 at 75°C. All enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 13 publications
(21 reference statements)
0
10
0
3
Order By: Relevance
“…[ 51 ] Aerosol sprays are more suitable for dressings with enzymatic components, because some of the wound healing enzymes can deactivate in the solution state. [ 57 ] An example aerosol spray, which included papain embedded pectin gel, was reported to soften dead skin and auto‐debride necrotic tissue. [ 57 ] Air or nitrogen can be used as an aerosol propellant for this new spray‐on dressing.…”
Section: Hydrogel‐based Burn Dressingsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 51 ] Aerosol sprays are more suitable for dressings with enzymatic components, because some of the wound healing enzymes can deactivate in the solution state. [ 57 ] An example aerosol spray, which included papain embedded pectin gel, was reported to soften dead skin and auto‐debride necrotic tissue. [ 57 ] Air or nitrogen can be used as an aerosol propellant for this new spray‐on dressing.…”
Section: Hydrogel‐based Burn Dressingsmentioning
confidence: 99%
“…[ 57 ] An example aerosol spray, which included papain embedded pectin gel, was reported to soften dead skin and auto‐debride necrotic tissue. [ 57 ] Air or nitrogen can be used as an aerosol propellant for this new spray‐on dressing. Nitrogen is superior to air, because air can negatively impact the enzymatic activity in wound healing.…”
Section: Hydrogel‐based Burn Dressingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute wounds that require intervention include mechanical abrasions, tear, surgical procedure, burns and chemical injuries. Chronic wounds include diabetic foot ulcers, pressure ulcers and leg ulcers (Boateng et al 2008;Jáuregui et al 2009). In general, acute wounds heal within 3 weeks while chronic wounds persist for more than 12 weeks and often reoccur.…”
Section: A Summary Of the Biology Of Wound Healingmentioning
confidence: 99%
“…The difference was calculated to be significant based on the Student´s t-test method with the resulting p <0.05. It was concluded that papain immobilized in pectin can be used for the development of effective aerosol spray system for wound healing in the areas of enzymatic debridement of necrotic tissue and liquefaction of slough to remove dead or contaminated tissue in acute and chronic lesions, such as diabetic ulcers, pressure ulcers, varicose ulcers, and traumatic infected wounds, postoperative wounds, burns, carbuncles, and pilonidal cyst wounds (Jáuregui et al, 2009). Lyofoam, polyurethane foam, is normally hydrophobic; however, when applying heat and pressure, it becomes hydrophilic and, in this form, while providing blood and exudates absorption, it also prevents drying the wound surface completely (Johnson et al, 1998;Catarino et al, 2000;Fenn & Butler, 2001;Lehnert & Jhala, 2005).…”
Section: Sprays and Foamsmentioning
confidence: 99%